Pemenuhan Nafkah bagi Pasangan Idiot di Karangpatihan Balong Ponorogo Jawa Timur - Linna Susanti (State Islamic University (UIN) of Sunan Ampel, 2014)
This article discusses about the implementation of compliance for idiot couples’ living in village Karangpatihan, Balong, Ponorogo within the perspective of Islamic law. Fulfillment of the idiot husband living in village Karangpatihan, Balong, Ponorogo obtained by working odd job with wages of around Rp. 6.000, - up to Rp. 20.000, per day. But the most commonly accepted salary is Rp. 6.000, -. This earning is only able to meet the food need to taste with the advanced food and snack for the children. This minimal income is deemed sufficient by his wife and idiot family, because they understand the limitation of their clothing. Idiot husband never buys clothes for his wife and children. It is their brothers who buy clothes for them. For residence, the idiot couple is still alive with their parents and brother. The implementation of a living fulfillment of the idiot husband to his family is not prohibited by Islamic law that ordered husband to provide a living according to his ability. Husband provides a living by taking into account to his family circumstance adapted to the ability of the husband and his family economic condition.